Treatment of Hypertension with Clonidine. Issue 5720 (22nd August 1970) - Macdougall, A. I.; Addis, G. J.; Mackay, N.; Dymock, I. W.; Turpie, A. G. G.; Ballingall, D. L. K.; Maclennan, W. J.; Whiting, B.; Macarthur, J. G.
Abstract : Clonidine, in a daily dosage of 0·15-4·8 mg., effectively lowered systolic and diastolic pressures in 26 out of 28 impatients with moderate to severe hypertension, including five with primary renal disease. The action of the drug did not depend on posture and was not associated with reduction in renal function. Side-effects were not severe, but mental changes occurred in four patients. Clonidine is a useful alternative to currently available antihypertensive drugs, but further evaluation of its longterm efficacy is required.